(untitled) (ACME, 2024)
This paper deals with the problem of interactions between Roman citizens and indigenous people in the territory of Bergomum, a municipium in regio xi - Transpadana, through the study of significant onomastic formulae appearing in some inscriptions. In particular, the analysis of the epigraphic evidence will work on a double track, taking into account indigenous onomastic structures – which we can still find in the first century CE, despite the fact that Caesar granted citizenship to Transpadana in the middle of the first century BCE – together with names in the typically Roman form of the tria nomina, which show a Celtic origin and a certain persistence of local customs. Thus, the evidence provided by onomastics will be useful for investigating how the “indigenous” inhabitants of Bergomum dealt with the progressive Romanization of their territory and through what mechanisms they were integrated into the Roman social structure. This will also be done through a comparison with nearby realities (such as the Colonia Civica Augusta Brixia).